Espaces à risque et marges : méthodes d’approche des vulnérabilités urbaines à Lima et Quito - Alexis Sierra (Cybergeo, 2009)
To analyze risk through space in Quito and in Lima, the author chose a geopolitical way comparing the different social perceptions of risk, and especially the causes, between stakes and vulnerability reasons. The article shows how the risk’s spaces are assimilated to deprived areas carrying stigma. The stigma’s analysis collaborating with geosciences is a way to understand social and political characteristics of risk and to identify risk as a territorialisation’s tool of deprived areas.